2011
DOI: 10.1021/nn202458g
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of the Protein Corona around Nanoparticles: A Test Study

Abstract: The importance of the protein corona formed around nanoparticles upon entering a biological fluid has recently been highlighted. This corona is, when sufficiently long-lived, thought to govern the particles' biological fate. However, even this long-lived "hard" corona evolves and re-equilibrates as particles pass from one biological fluid to another, and may be an important feature for long-term fate. Here we show the evolution of the protein corona as a result of transfer of nanoparticles from one biological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
632
0
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 723 publications
(669 citation statements)
references
References 30 publications
20
632
0
9
Order By: Relevance
“…Protein‐induced nanomaterial aggregation was also reported in our previous study, wherein electrostatic attraction triggered the agglomeration of serum albumin molecules and carbon nanotubes 17. However, due to the effect of “dynamic adsorption balance,”18 excess protein would not cause the unlimited increase in nanomaterial aggregation. That was why the hydrated particle size of C‐GNR bioconjugates became stable at around 180 nm when the protein concentration was increased to 4 × 10 −5 m .…”
Section: Resultssupporting
confidence: 68%
“…Protein‐induced nanomaterial aggregation was also reported in our previous study, wherein electrostatic attraction triggered the agglomeration of serum albumin molecules and carbon nanotubes 17. However, due to the effect of “dynamic adsorption balance,”18 excess protein would not cause the unlimited increase in nanomaterial aggregation. That was why the hydrated particle size of C‐GNR bioconjugates became stable at around 180 nm when the protein concentration was increased to 4 × 10 −5 m .…”
Section: Resultssupporting
confidence: 68%
“…This modification of the adsorbed proteins in NP-PCs may involve specific foldings, which may lead to a change in the conformation of the epitopes of the adsorbed protein. 40 Moreover, nanoparticles can change continuous epitopes of the adsorbed protein, affecting a stretch of 10-12 amino acids, and this stretch is capable of eliciting an immune response. Thus, by forming NP-PCs in biological systems, nanoparticles can induce an abnormal unfolding of adsorbed proteins, which may result in an unwanted immune response through the exposure of hidden epitopes.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, it was also found to be the most abundant protein in the hard corona of silica NPs, 59 while in other cases, its content in the hard protein corona was very low. [60][61][62] Physical parameters such as the surface curvature of NPs were proposed to play a role in the competitive adsorption of proteins in the process, resulting in the formation of the hard corona. 22 It could be of interest to investigate the possible contribution of different amounts and distributions of surface silanols to the composition of the hard protein corona on SiO 2 NPs.…”
Section: Cd-uv Spectra Of Irreversibly Adsorbed Proteinsmentioning
confidence: 99%